Aktivitas Antimikroba Sabun Antiseptik Bunga Eceng Gondok (Eichhornia crassipes) dengan Basis Minyak Jelantah - Nangsih Sulastri Slamet; Fihrina Mohamad; Hartati Hartati; Fadli Husain; Zulfiayu Sapiun (Fakultas Farmasi Universitas Pancasila, 2022)
Water hyacinth flowers (Eichhornia crassipes) contain antibacterial phenols, flavonoids, alkaloids, tannins, terpenoids, sterols, and glycosides that can be made into antiseptic soaps. Used cooking oil purifi ed with banana peel can be used to make soap. This study aimed to determine how to process used cooking oil, formulate and test antimicrobial antiseptic soaps using water hyacinth flower extract. The method uses antiseptic soap formulated with 10%, 15%, and 20% water hyacinth infusion. Physical, chemical, irritation, and antibacterial testing of the preparation. Used cooking oil is refined and clear, not thick. Water hyacinth flower extract can be formulated into antiseptic soap with a 1.5 cm foam height, cleaning power in criteria 3, pH in the range 9-10, water content >15%, and free alkali content of 0.6- 1.3%. Formula A (19.17 mm), B (20.01 mm), and C have strong antibacterial activity against E. coli based on the diameter of the barrier (20.13 mm). Water hyacinth flower extract and used cooking oil can be used to make antimicrobial antiseptic soap.